2013
DOI: 10.4306/pi.2013.10.3.294
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of IL-23 and IL-17 before and after Antidepressant Treatment in Patients with Major Depressive Disorder

Abstract: ObjectiveCytokines are believed to have a role in the pathophysiology of major depression. The alteration in levels of pro-inflammatory cytokines [interleukin 1β (IL-1β), IL-2, IL-6, IL-12, interferon γ, and tumor necrosis factor α] in major depression supports the cytokine hypothesis of this illness. IL-23 and IL-17 are also pro-inflammatory cytokines, but few studies have focused on their role in major depression. This study investigated the potential role of the IL-23 and IL-17 axis in major depression.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 36 publications
4
40
2
Order By: Relevance
“…Few studies, however, have investigated the connection between depression and high levels of IL-17. In the study of Han et al [41], levels of IL-17 and IL-23 were measured in the plasma of patients with severe depression, but no correlation was found. In contrast, Liu et al [57] found a link between high IL-17 levels and depression, but they investigated patients with rheumatoid arthritis (RA).…”
Section: Does Il-17 Have a Role In Depression?mentioning
confidence: 96%
“…Few studies, however, have investigated the connection between depression and high levels of IL-17. In the study of Han et al [41], levels of IL-17 and IL-23 were measured in the plasma of patients with severe depression, but no correlation was found. In contrast, Liu et al [57] found a link between high IL-17 levels and depression, but they investigated patients with rheumatoid arthritis (RA).…”
Section: Does Il-17 Have a Role In Depression?mentioning
confidence: 96%
“…In order to explore whether fluoxetine effects on inflammation depend on the quality of the living environment, we analyzed hippocampal expression levels of seven immune mediators reportedly involved in antidepressant drug action (Carvalho et al, 2013;Chen et al, 2010;Eller et al, 2008;Hannestad et al, 2011;Kim et al, 2013;Lanquillon et al, 2000;Song et al, 2009;Tuglu et al, 2003) and affected by environmental stimuli (Chabry et al, 2015;Goshen et al, 2008;Singhal et al, 2014;Wohleb et al, 2011). In particular, we focused on IL-6, TNFα and IL-1β, which are pro-inflammatory cytokines among the most studied in relation to antidepressant effects (Carvalho et al, 2013;Eller et al, 2008;Hannestad et al, 2011).…”
Section: Fluoxetine Affects Hippocampal Inflammatory Mediatorsmentioning
confidence: 99%
“…However, other clinical studies obtained opposite results, demonstrating no or even pro-inflammatory effects of antidepressant treatment (Chen et al, 2010;Haastrup et al, 2012;Hannestad et al, 2011;Jazayeri et al, 2010;Kim et al, 2013;Song et al, 2009). Experimental studies reflect the incongruence of clinical findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, based on the presented data, it may be concluded that one of the main mechanisms of these drugs is to downregulate IL-17A expression and to diminish the number of Th17 lymphocytes. In contrast, there are studies revealing that some antidepressant drugs lack these effects; for instance, Kim et al reported that serum levels of IL-17A and its related cytokine, IL-23, were not altered after antidepressant treatment (32). Furthermore, it has been established that ladasten is unable to change the expression of IL-17A in mice with experimental depression-like syndrome (33).…”
Section: Il-17a and Depressionmentioning
confidence: 99%